Metal-catalyzed regiodivergent organic reactions - Nájera, Carmen; Beletskaya, Irina P; Yus, Miguel (Chemical Society reviews, 2019)
Metal-catalyzed regiodivergent reactions allow control over regioselectivity in the synthesis of a wide range of organic products. Starting from the same material, it is possible to prepare different regioisomers just by appropriately choosing the catalyst or by modifying the reaction conditions. Therefore, these regiodivergent methodologies should be included as the key factor in the concept of efficiency and atom economy in synthetic organic chemistry. The synthetic potential of this subject has been demonstrated mainly in addition reactions to unsaturated carbon-carbon bonds, allylic and propargylic nucleophilic substitutions, C-H activation reactions, cross-couplings, and intramolecular or intermolecular cyclizations. This review article overviews the development and rationalization of regiodivergence in these fundamental reactions in the last 15 years. This review discusses metal-catalysed regiodivergent additions, allylic substitutions, CH-activation, cross-couplings and intra- or intermolecular cyclisations.